2021
DOI: 10.1097/scs.0000000000007761
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Dissection Direct Frontalis Muscle Advancement Flap for Congenital Ptosis Repair

Abstract: Background: Frontalis flap advancement is an alternative means of congenital ptosis repair from frontalis suspension utilizing autologous fascia or allogenic implants. Variations in technique, including flap division, location and number of skin incisions, and dissection planes, are described in the literature. Materials and Methods: A retrospective case series of patients with congenital myogenic ptosis treated with simplified, minimal dissection frontalis flap advancement involving a single upper eyelid crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Plastic and Reconstructive Surgery • November 2023 886e the original eyelid crease and infrabrow double incisions, [6][7][8][9][10][11] the eyelid crease single-incision has become the most popular incision design over the past decade because of fewer scars. [12][13][14][15][16][17][18][19] However, the conventional frontalis muscle advancement technique still has some disadvantages, such as residual lagophthalmos (RL); eyebrow ptosis; eyelid contour abnormality; and especially, undercorrection, with a median value of 12.2%. 3,[10][11][12][13][14] Insufficient separation leads to poor flap mobility, which may be the main reason of RL, eyebrow ptosis (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plastic and Reconstructive Surgery • November 2023 886e the original eyelid crease and infrabrow double incisions, [6][7][8][9][10][11] the eyelid crease single-incision has become the most popular incision design over the past decade because of fewer scars. [12][13][14][15][16][17][18][19] However, the conventional frontalis muscle advancement technique still has some disadvantages, such as residual lagophthalmos (RL); eyebrow ptosis; eyelid contour abnormality; and especially, undercorrection, with a median value of 12.2%. 3,[10][11][12][13][14] Insufficient separation leads to poor flap mobility, which may be the main reason of RL, eyebrow ptosis (Fig.…”
mentioning
confidence: 99%
“…3,10 The subcutaneous separation range of the conventional frontalis muscle flap is usually limited and does not exceed 1 cm above the superior margin of the eyebrow because of the limited visualization and uncertainty with the surgical anatomy of the forehead, as seen through the eyelid crease incision. [13][14][15][16][17][18][19] Recent understanding of the forehead anatomy, in particular, the description of the forehead compartments, 20 has provided the knowledge to harvest extended frontalis muscle flap with more certainty, safety, and predictability through the eyelid crease incision. The superficial forehead compartments are located in the subcutaneous fat layer of the forehead.…”
mentioning
confidence: 99%
“…Severe and moderate PEEs were not found in any patient. Lagophthalmos ≥ 1 mm was more common in the TCMLR group in all three follow-ups, but the difference was not statistically significant [12,12,13 cases in TCMLR group and 11, 12, 11 cases in frontalis sling group in 1, 3, 6mo followups respectively (P=1)]. Furthermore, the lid lag > 3 mm was statistically similar in both groups [19,19,19 cases in TCMLR group and 21, 22, 22 cases in frontalis sling group in 1, 3, 6mo follow-ups respectively (P=1)].…”
Section: Resultsmentioning
confidence: 68%
“…S evere unilateral congenital ptosis with poor levator function (LF) is the most challenging category of congenital ptosis varieties [1][2] . Frontalis sling is the choice procedure for congenital ptosis with poor LF, which could be performed by different materials such as silicone rod, sutures, frontalis muscle flap, temporalis fascia, fascia lata and etc [1,[3][4][5][6][7][8][9][10][11][12][13][14][15] . Although unilateral ptosis frontalis sling surgery does not achieve perfect eyelid function and cosmetic appearance as well as bilateral ones [3] .…”
Section: Introductionmentioning
confidence: 99%
“…This result also showed that there was no significant difference between the two groups in comparing the cosmetic results at 1, 6 and 12 months after surgery. This may be due to the fact that the clinical use of the frontalis muscle flap for suspension has good elasticity, high muscle strength, and the operator can adjust the lid curvature according to the actual situation of the child, As a result, the double eyelid curvature after surgery is well formed, the appearance is natural, and the effect is lasting ( 22 24 ); Instead, the e-PTFE frontalis suspension surgery uses individualized double eyelid surgery, the surgeon tried to bury the e-PTFE material under the muscle as much as possible during the operation, and the broken end of the material is directly sewn with sutures firmly to increase the flatness, in addition, e-PTFE has excellent biocompatibility and extensibility, stable chemical properties, slow degradation rate, and long retention time, which is conducive to maximizing the postoperative aesthetic effect and long-term maintenance of children.…”
Section: Discussionmentioning
confidence: 99%